Absence of the Drosophila jump muscle actin Act79B is compensated by up‐regulation of Act88F. Issue 4 (6th February 2018) - Dohn, Tracy E.; Cripps, Richard M.
Abstract : Background: Actins are structural components of the cytoskeleton and muscle, and numerous actin isoforms are found in most organisms. However, many actin isoforms are expressed in distinct patterns allowing each actin to have a specialized function. Numerous studies have demonstrated that actin isoforms both can and cannot compensate for each other under specific circumstances. This allows for an ambiguity of whether isoforms are functionally distinct.Results: In this study, we analyzed mutants of Drosophila Act79B, the predominant actin expressed in the adult jump muscle. Functional and structural analysis of the Act79B mutants found the flies to have normal jumping ability and sarcomere structure. Analysis of actin gene expression determined that expression of Act88F, an actin gene normally expressed in the flight muscles, was significantly up‐regulated in the jump muscles of mutants. This indicated that loss of Act79B caused expansion of Act88F expression. When we created double mutants of Act79B and Act88F, this abolished the jump ability of the flies and resulted in severe defects in myofibril formation.Conclusions: These results indicate that Act88F can functionally substitute for Act79B in the jump muscle, and that the functional compensation in actin expression in the jump muscles only occurs through Act88F . Developmental Dynamics 247:642–649, 2018 . © 2018 Wiley Periodicals, Inc. Key Findings: Mutants for the Drosophila jump muscle actin gene show expansion of expression of the flight muscle actin gene into the jump muscles, demonstrating paralogous compensation. These mutants jump normally, demonstrating some functional overlap between the different genes. Flies mutant for both genes cannot jump, indicating that the paralogous compensation only occurs between these two genes.